Skrifgeloof en regswetenskap - Raath, A. W. G. (Koers, 1986)
This article deals with the fundamental value of the Bible for the scientific stud y of the law according to the Philosophy of the idea of Creation. A stud y of the law in the light of the motive of creation, the fall of man and the redemption of man through Christ Jesus, provides the correct context and perspective for revealing legal principles. The author further more explains that humanistic approaches to the law do necessarily come to different conclusions than does the Calvinistic philosophy of law.